Market Positioning & Operational Strategy To Start Home Goods Retail Business In Indonesia - Yuwei, Liu (Green Publisher Indonesia, 2024)
The growing need for affordable yet quality household goods offers a great opportunity for retail businesses to cater to the needs of consumers and the small to medium enterprise (SMB) sector. This research aims to explore the market positioning and operational strategies in starting a home furnishing retail business in Indonesia, with a focus on the lower-middle class and SMB segments. The research method involved analyzing the operational strategies of retail companies in Indonesia to identify key success factors and potential growth opportunities. Research data was obtained through online data sources, industry reports, market research, policy documents, as well as primary data from the researcher's professional experience and related academic research. The research results propose a strategy based on the concept of “people, goods, and space” to improve customer experience, operational efficiency, and brand loyalty. The business model starts with a pilot store in Semarang before expanding to other major cities through direct operation and franchising models. The B2B segment leverages the supply chain to provide customized solutions for SMBs. Key operational elements include strategic location, comprehensive SOPs, local marketing, and partnerships with trusted providers. The research also recommends long-term growth strategies, including adaptation to dynamic market trends, integration of customer feedback, and implementation of sustainable supply chain practices. The results of this study are expected to serve as a strategic guide for creating a competitive and responsive home furnishing retail business in the rapidly growing Indonesian market.